Intermediate-state-trapped mutants pinpoint G protein-coupled receptor conformational allostery - Xudong Wang; Chris Neale; Soo-Kyung Kim; William A. Goddard; Libin Ye (Nature Communications, 2023)
Understanding of GPCR activation is limited as the structural information fails to present the full spectrum of energy landscape. Here, authors establish a series of conformation-biased mutants that represent five conformational states lying along adenosine A2A receptor (A2AR) activation.